2012
DOI: 10.1371/journal.pone.0030088
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of Genes Encoding Granule-Bound Starch Synthase in Monocots and Dicots Is Marked by Multiple Genome-Wide Duplication Events

Abstract: Starch is one of the major components of cereals, tubers, and fruits. Genes encoding granule-bound starch synthase (GBSS), which is responsible for amylose synthesis, have been extensively studied in cereals but little is known about them in fruits. Due to their low copy gene number, GBSS genes have been used to study plant phylogenetic and evolutionary relationships. In this study, GBSS genes have been isolated and characterized in three fruit trees, including apple, peach, and orange. Moreover, a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 48 publications
1
34
1
Order By: Relevance
“…Palm and banana SSII genes might have been duplicated prior to Commelinid lineage divergence while grass GBSS could have originated from a monocot ancestral duplication ( Figures 3 and 4 ). The timing of monocot GBSSI/GBSSII duplication is unclear since our GBSS tree topology differed from previously published ones (Cheng et al, 2012) which suggested a shared ancestral GBSS duplication between eudicots and monocots thus predating eudicot/monocot split. The identification of eudicot GBSSII and GBSSI genes on grapevine syntenic blocks implies that they originated from the gamma hexaploidization (Jaillon et al, 2007) that is at the root of eudicot radiation.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Palm and banana SSII genes might have been duplicated prior to Commelinid lineage divergence while grass GBSS could have originated from a monocot ancestral duplication ( Figures 3 and 4 ). The timing of monocot GBSSI/GBSSII duplication is unclear since our GBSS tree topology differed from previously published ones (Cheng et al, 2012) which suggested a shared ancestral GBSS duplication between eudicots and monocots thus predating eudicot/monocot split. The identification of eudicot GBSSII and GBSSI genes on grapevine syntenic blocks implies that they originated from the gamma hexaploidization (Jaillon et al, 2007) that is at the root of eudicot radiation.…”
Section: Discussioncontrasting
confidence: 87%
“…SSI genes and homologs of the functional AtSS4 gene (SSIV) were mostly single copy in analyzed angiosperm species. The SSII and SSIII genes were found as single copy genes in sampled Eudicots but were duplicated in banana and also, as previously described, in grasses (Wu et al, 2008; Yan et al, 2009; Cheng et al, 2012). In addition, date palm SSII genes were also found duplicated ( Figure 4 ).…”
Section: Resultssupporting
confidence: 74%
“…GBSSI or waxy gene expresses exclusively in storage tissues such as seed endosperm and embryo, while the GBSSII gene is transcripted mainly in non-storage tissues such as leaf, stem, root, and pericarp (Dry et al 1992; Vrinten and Nakamura 2000; Dian et al 2003). In addition, other different isoforms of GBSS have also been reported in eudicot species (pea, orange, apple and peach), and have various expression profiles differing in cereals (Denyer et al 1997; Edwards et al 2002; Szydlowski et al 2011; Cheng et al 2012). While validating the normalized qRT-PCR system, we explored and confirmed the tissue specificity of SiSS gene in sesame.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by evidence of common domestication alleles in both japonica and indica . The second theory proposes multiple independent domestications (Choi et al, 2017;Kumagai et al, 2016). This is attractive due to the significant genetic distance between japonica and indica clades estimated to be around 1 million years.…”
Section: Introductionmentioning
confidence: 99%
“…This is an area without a long history of rice cultivation, implying that the wild populations have remained largely isolated from the impacts of gene flow from domesticated crops that has apparently been widespread in Asia (Brozynska et al, 2017). The AA genome species of rice include cultivated species and their close relatives (Choi et al, 2017). Draft genome sequences of the AA genome populations from…”
Section: Introductionmentioning
confidence: 99%